Gender, health and women rights in India - Manimaran*, K. (International Multidisciplinary Research Journal, 2011)
The necessity of good Health of women, Nutrient Agents, and important preservation of women Health is gives detailed account of minerals, phosphorus, Magnesium, Daily requirements of minerals, carbohydrates. It should be stretches to human life, Proteins, how many calories they have for good health, vitamins like B, C, A, E and K- How much energy women have. Approximate daily diets allowances, Ã¢â‚¬Å“Various Rights offered to women development in Education and various Acts passed by the Government of India and Tamil Nadu State Government for the welfare of women.